Rebels at the bar : the fascinating, forgotten stories of America's first women lawyers - Norgren, Jill (New York : New York University Press, 2016)
This text recounts the life stories of a small group of nineteenth-century women who were among the first female attorneys in the United States. Beginning in the late 1860s, these determined rebels pursued the radical ambition of entering the then all-male profession of law. They were motivated by a love of learning. They believed in fair play and equal opportunity. They desired recognition as professionals and the ability to earn a good living. The book presents the common struggles of eight women first to train and to qualify as attorneys, then to practice their hard-won professional privilege. Their story is one of nerve, frustration, and courage.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Women lawyers -- United States -- Biography; Women lawyers -- United States -- History -- 19th century; Biography; United States of America, USA; Biography & non-fiction prose; Collected biographies; History of the Americas; Jurisprudence & general issues